Development of a Direct Adaptive PID Controller for a Quadruped Robot - Bui, Mạnh Huy; Pham, Tấn Phát; Nguyen, Trần Minh Nguyệt; Dang, Xuân Ba (Journal of Technical Education Science, 2022)
Recently, research on quadruped robots has not gotten much attention in Vietnam due to complicated mechanical structures of the robots as well as unstructural working environments. Employment of simple control methods such as Proportial-Integral-Derivative (PID) controllers for such the systems is feasible but the control performances have not been maintained in some cases that could make the robots danger. Obviously, the complicated controllers seem to be promissing if the system is equipped with strong hardware. In this paper, we propose a new adaptive Jacobian-based PID controller for low-level control of a quadruped robot system that could possibly be deployed into low-cost hardware. The proposed controller is first built on a conventional PID structure. To suppress internal/external dynamics of the robot in various working conditions for a minimal control error, a nonlinear adaptive rule is then integrated to update the control gains. Effectiveness and feasiblity of the designed controller are intensively verified in a simulation enviroment. The comparative results obtained confirm that the proposed controller is simple, adaptive, robust and efficient.